Revised Statutes of the State of Arkansas, Adopted at the October Session of the General Assembly of Said State, A.D. 1837, at 733-34 (1838) - (:unkn) unknown (General Publisher, 1838)
Prohibited any “free negro” from possessing or carrying a gun, ammunition, or weapon of any kind without a license.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES